Pengaruh Isu Politik, Desain Pesan, Media Komunikasi dan Gangguan Media Komunikasi Terhadap Partisipasi Politik - Jannah, Anata; Sangun, Enisar; Prasetya, Hendri (Jurnal Pustaka Komunikasi, 2023)
This research was inspired by the phenomenon of low political participation associated with political messages in the mass media. The purpose of this study was to determine the effect of political issues, message design, communication media and communication media disturbances on political participation. This study used a quantitative method by distributing questionnaires to 106 respondents at SMAN 2 Lumajang. The Data was processed using Smart PLS. The results of the study stated that the three variables, political issues, message design and political communication disturbances had no effect on political participation. Only the communication media variable has an effect of 38% on political participation. Simultaneously, the variable message issue, message design, communication media and communication media disturbance have an effect of 21.5 percent on political participation. The remaining 78.5% of political participation variables are influenced by other variables outside of this study.